Physiotherapy Management in Cases of Bell's Palsy Dextra et Causa Post Craniotomy with Transcutaneous Electrical Nerve Stimulation (TENS) and Facial Exercise: Case Reports - Ramahandika, Achmad Kukuh; Widodo, Agus; Kadarti, Sri Isnin (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Bell's palsy is a condition of peripheral facial paralysis or weakness which is generally idiopathic, occurring due to interference with nerve VII in the stylomastoid foramen. Although the majority of patients recover completely, a small proportion experience different sequelae. Although its etiology is not yet fully understood, its association with certain viral infections has been recognized, causing neuroinflammation and other pathological processes. Risk factors such as elevated blood sugar, uncontrolled blood pressure, and migraines can increase susceptibility to this paralysis. Case Presentation: This study reported a men patient, 16 years old with bell's palsy dedxtra post craniotomy after an accident on November 2023 and there was bleeding in the brain. The patient was taken to Dr. Sardjito General Hospital for surgery and felt that the right side of his face was thickened, numb and sensitive after the operation. Management and Outcome:. The measuring instruments used in this study were the Numeric Rating Scale (NRS) to measure the degree of pain felt by the patient, Manual Muscle Testing (MMT) to measure the degree of muscle strength, Ugo fisch performed on patients to provide information regarding facial function assessment, and House-Brackmann Score to assess nerve damage in facial nerve paralysis and Transcutaneous electrical nerve stimulation intervention. Discussion: There was a decrease in pain as measured using a numeric rating scale from 3 to 2, an increase in muscle strength from 3 to 4, an increase in the degree of functional activity from 26 points (poor condition) to 50 points (medium condition), there was an increase in the score on the House- Brackmann Score from grade V (severe dysfunction) to grade IV (moderate and severe dysfunction). Conclusion: Comprehensive treatment with physiotherapy techniques has a positive effect on patients with Bell's Palsy. This research may be a reference to guide other physiotherapists in carrying out rehabilitation for Bell's Palsy patients.